Exploring the potential of dietary factors and plant extracts as chemopreventive agents in oral squamous cell carcinoma treatment - Madhav Kumar; Abhimanyu Kumar Jha (Frontiers Media S.A., 2023)
Oral cancer, particularly oral squamous cell carcinoma (OSCC), is a prevalent malignancy having a significant fatality rate worldwide. Despite advancements in conventional treatment modalities, the overall survival rate for OSCC remains low. Therefore, there is a critical need to explore alternative therapeutic approaches that can improve patient outcomes. This review focuses on the potential of dietary factors and plant extracts as chemopreventive agents in treating oral cancer. These compounds possess diverse biological functions encompassing a range of attributes, such as antioxidative, anti-inflammatory, and anticancer capabilities. By targeting multiple cellular pathways involved in carcinogenesis, they possess the capacity to hinder tumor growth and development, promote programmed cell death, and impede the progression of oral cancer. Signaling pathways targeted by natural compounds that have been included in this review include Akt/mTOR/NF-κB signaling, Hippo-Tafazzin signaling pathway, notch signaling pathway, mitochondrial pathway, and Sonic Hedgehog pathway.